Morphology and molecular phylogeny of epizoic araphid diatoms on marine zooplankton, including Pseudofalcula hyalina gen. & comb. nov. (Fragilariophyceae, Bacillariophyta) - Gómez, Fernando (Journal of phycology, 2018)
© 2018 Phycological Society of America.